Analysis of atopic diseases incidence among the children population. - V. O. Dytiatkovskyi; A. A. Kuliyeva; K. P. Bovsunovs`ka (Medičnì Perspektivi)
The paper provides analysis of atopic diseases incidence diagnosed in children. There have been analyzed the associations between genesis of atopic diseases and child`s age, spectrum of cause-significant allergens, presence of digestive tract comorbidities. There have been given the recommendations for personalizing diagnostics and treatment of children having allergy manifestations on the background of the digestive tract diseases.